Host inflammatory response is the major factor in the progression of Chlamydia psittaci pneumonia - Zhang, Zhenjie; Wang, Peihan; Ma, Chuanmin; Wang, Jing; Li, Wenxin; Quan, Chuansong; Cao, Huae; Guo, Hongfeng; Wang, Liang; Yan, Chengxin; Carr, Michael J.; Meng, Ling; et al. (Frontiers in Immunology, 2022)
Purpose: Chlamydia psittaci (C. psittaci) has caused sporadic, but recurring, fatal community-acquired pneumonia outbreaks worldwide, posing a serious threat to public health. Our understanding of host inflammatory responses to C. psittaci is limited, and many bronchitis cases of psittaci have rapidly progressed to pneumonia with deterioration. Methods: To clarify the host inflammatory response in psittacosis, we analyzed clinical parameters, compared transcriptomic data, concentrations of plasma cytokines/chemokines and changes of immune cell populations in 17 laboratory-confirmed psittacosis cases, including eight pneumonia and nine bronchitis individuals, in order to assess transcriptomic profiles and pro-inflammatory responses. Results: Psittacosis cases with pneumonia were found to have abnormal routine blood indices, liver damage, and unilateral pulmonary high-attenuation consolidation. Transcriptome sequencing revealed markedly elevated expression of several pro-inflammatory genes, especially interleukins and chemokines. A multiplex-biometric immunoassay showed that pneumonia cases had higher levels of serum cytokines (G-CSF, IL-2, IL-6, IL-10, IL-18, IP-10, MCP-3 and TNF-α) than bronchitis cases. Increases in activated neutrophils and decreases in the number of lymphocytes were also observed in pneumonia cases. Conclusion: We identified a number of plasma biomarkers distinct to C. psittaci pneumonia and a variety of cytokines elevated with immunopathogenic potential likely inducing an inflammatory milieu and acceleration of the disease progression of psittaci pneumonia. This enhances our understanding of inflammatory responses and changes in vascular endothelial markers in psittacosis with heterogeneous symptoms and should prove helpful for developing both preventative and therapeutic strategies.